(untitled) (CIPEEX, 2026)
The consolidation of Artificial Intelligence as a strategic field for the 21st century demands innovative academic training capable of integrating theoretical foundations, applied practices, and social impacts. In this context, UniEVANGÉLICA’s Bachelor’s Degree in Artificial Intelligence adopts Project-Based Learning (PBL) as the central axis of its pedagogical approach, organizing the educational path into cycles of integrative projects that combine teaching, research, and outreach. This methodological shift, however, requires a significant transformation in the teaching profession. The teacher ceases to be a mere transmitter of content and assumes the role of mediator, mentor, and facilitator of complex learning, needing to adapt to the new demands of increasingly active, critical, and connected students. This repositioning requires constant updating, interdisciplinarity, and the ability to streamline classroom interactions, fostering a collaborative and participatory environment. This summary discusses this new teaching role within the context of the program, reflecting on the necessary competencies and sharing four testimonials from first-year undergraduate teachers who share their experiences, challenges, and lessons learned. The conclusion is that PBL profoundly impacts teaching identity and practice, requiring professional reinvention and openness to collaborative learning.